Nursing art as a practical art: the necessary relationship between nursing art and nursing ethics - Blondeau, Danielle (Nursing philosophy, 2002)
In the last decade, nurse scholars have focused extensively on the nature of nursing and its relationship to art and science. This emphasis has also been accompanied by an increasing literature on nursing ethics. In spite of this growing interest, the relationship of nursing art and nursing ethics has been left unclear. This paper proposes that nursing must be considered as a practical art because this conception explicates the relationship of nursing art and nursing ethics. It is based on the thesis that nursing art is subordinated to nursing ethics and as such is a moral art. Different conceptions of nursing art (craft and fine art) will be explored to show their limits. This will be followed by the conception of nursing art as a practical art.